Metallography in Archaeology and Art - Scott, David A.; Schwab, Roland (Cultural Heritage Science,, 2019)
This book provides a comprehensive introduction to the metallographic study of ancient metals. Metallography is important both conceptually as a microstructural science and in terms of its application to the study of ancient and historic metals.   Metallography is a well-established methodology for the characterization of the microstructure of metals, which continues to be significant today in quality control and characterization of metallic properties. Not only does the metallographic examination of ancient metals present its own challenges in terms of sample size and interpretation of evidence, but it must be integrated with archaeological data and cultural research in order to obtain the most meaningful results. Issues of authentication and the establishment of fakes and forgeries of metallic artefacts often involve metallographic evidence of both metal and patina or corrosion interface, as an essential component of such a study. The present volume sets out the basic features of relevant metallic systems, enhanced with a series of examples of typical microstructural types, with illustrative case studies and examples throughout the text derived from studies undertaken by the two authors. This book provides a comprehensive presentation of metallography for archaeologists, archaeometallurgists, conservators, conservation scientists and metallurgists of modern materials. .